Planting for food and jobs participation and its impact on maize productivity in Ghana: implications for research and policy - Edward A. Awafo; Ernest Christlieb Amrago; Emmanuel Amankwah; Gilbert Ayine Akolgo (Cogent Social Sciences)
To foster maize productivity and advance agricultural development, the Government of Ghana (GoG) has enacted several flagship programmes as a response to the pressing need to improve the sector. Planting for food and jobs (PFJ) is one such programme. This study investigates the impact of PFJ participation on maize productivity and income amongst maize farmers in northern Ghana. The study sampled 384 maize farmers. Cross-sectional data were collected and analysed using the probit model, propensity score matching, and Dolby robust estimator. The estimation shows that PFJ participation had a positive effect on maize productivity and farmers’ income. It was also observed that PFJ participation was influenced by gender, farming experience, education, access to credit, cooperative membership, and farm distance. Limited fertilizer access and restricted market access were the major challenges that militated against PFJ programme participation. Thus, Government of Ghana (GoG), through the Ministry of Food and Agriculture (MoFA), prioritised the provision of subsidised fertiliser to farmers who would otherwise struggle to purchase enough fertiliser to increase productivity and income. This could greatly reduce the impact of the crowding out phenomenon on the PFJ programme.